Caral-Supe y su entorno natuural y social en los origenes de la civilizacion - Shandy Solis, Ruth (2005)
We began our archaeological research on the origins of civilization in Peruin 1994 with esploration in the Supe Valle and excavation in Caral in 1996; in both cases thiis work stemmed from a personal initative and was supported by of a team of archaecologists. Subsequently , in 1999, in view of the firstresultl that had been published in Peru and abroad, the University of San Marcos added its finalcial support to the finds already being provied by the Municipalities of Supe and Barranca . Once Caral was officially recongized as a site of national interest in 2001,two years later the Caral-Supe Special,Archeological Project (PEACS) was created; excavation work in Caral and three other sites has been intensified and consolidation and restoration work is now under way; In addition, we have drawn up a Master Plan and there are projects currently in execution to ensure that the important cultural heritage of Caral is presented in the most appropriate natural and context.